PERBEDAAN TINGKAT KEUNTUNGAN USAHA TANI PADI SAWAH MENGGUNAKAN MESIN POWER THRESHER DAN COMBINE HARVESTER DI DESA SANGATTA SELATAN - Istikomah, Istikomah -; Rusmiyati, Rusmiyati; Firmandari, Ratih Dinar (AGROTEKSOS; Vol 32 No 3 (2022): Jurnal Agroteksos Desember 2022, 2022)
The purpose of this study was to determine the difference in income earned by Lowland Rice Farming with Power Threshers and combine harvesters in South Sangatta Village, South Sangatta District. The method of data analysis technique used is quantitative data through economic analysis: cost analysis, income and revenue analysis is an activity after data from all respondents. The research population is paddy rice farmers. The sampling method used purposive sampling, rice farmers who were sampled deliberately only used power thresher harvesters as many as 25 farmers and combine harvesters as many as 20 people in South Sangatta Village, South Sangatta District. The data used is primary data, namely costs input costs of farming, total production of lowland rice, receipts and income of lowland rice farming using power threshers and combine harvesters. Secondary data BPS from 2018-2020 . The results of the study showed that the income of lowland rice farming using a power thresser machine amounted to Rp. 202,950,000 on average Rp. 8,118,000 while the combine harvester machine amounted to Rp. 133,050,000 for an average of IDR 8,870,000. The income of lowland rice farming using a power thresser machine is 78,873,333 with an average of Rp. 3,153,493 while the combine harvester machine is 69,194,879 with an average of Rp. 4,612,991. The Profit Rate (R/C Ratio) of farming using a power thresher is 1.63 while the combine harvester is 2.08 Lowland rice farming in South Sangatta Village is profitable. The use of Combine Harvester harvesting equipment is more profitable based on the value of the R/C ratio which is greater than the power thresher. Its because harvesting with a combine harvester does not require harvester labor costs .